BEM-ESTAR NO TRABALHO: O IMPACTO DOS VALORES ORGANIZACIONAIS, PERCEPÇÃO DE SUPORTE ORGANIZACIONAL E PERCEPÇÕES DE JUSTIÇA - Covacs, Jorge Miguel Luiz de Macedo (2006)
The increasing complexity of the workplace has demanded adaptive capabilities from employees including greater exigencies for more flexibility and creativity in dealing with and overcoming presenting challenges. Shorter product life cycles in an increasingly aggressive market have exerted tremendous pressure on employees, with subsequent health related side effects, including psychosomatic diseases and stress. Treating such ailments, although relevant in minimalizing individual human suffering, has proven insufficient in providing alternatives for the work-place environment from the health care standpoint as to include overall well-being and challenge-coping skills for employees. Positive psychology, interested in people development studies, allows organizations, managers, and employees to broaden options in dealing with people’s health issues in a way to positively impact organizations. The objective of this study is to confirm whether organizational values, perceived organizational support, and perceptions of (distributive and procedural) justice are antecedents of well-being in the work place, as measured by a construct of distinct variables of work-place satisfaction rates, job involvement, and affective organizational commitment. The sampling involved 404 workers from the metropolitan area of São Paulo, including 209 males and 193 females. The sampling was split into two entrepreneurial fields, half of which working in the financial market (composed of one single company corresponding for 243 subjects) and the other half not in the financial market (composed of 13 different companies corresponding for 161 subjects). As data gathering tool the author used a composite sevenscale questionnaire including three workplace well-being variables and four independent variables studied as its antecedents. Results demonstrate that both the perceptions of organizational support and distributive and procedural justice perception engendered a correlated increase in job satisfaction and affective organizational commitment. The organizational value autonomy have been confirmed as job involvement antecedent. The organization value realization and procedural justice perception have been confirmed as a organizational commitment antecedent for the non-financial and the financial samples respectively. Results show that well-being in the workplace is promoted when organizations implement supportive and dignifying treatment policies and practices towards employees, where organizational values that sustain an innovation-and-creativity-friendly environment and meritocracy are strengthened and where organization-employee relations are encouraged by sincerity and honesty. Employees will, thusly, tend to develop healthy social exchange based on trust and loyalty while investing their efforts for the organization